2021
DOI: 10.1093/ibd/izab007
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Fatigue in Inflammatory Bowel Disease

Abstract: Background Fatigue is one of the most frequently reported symptoms by patients with inflammatory bowel disease (IBD), both during active disease phases as well as during clinical remission. This study addressed whether different trajectories of fatigue over time can be identified among patients with IBD. Subsequently, we compared the demographic and clinical characteristics between trajectories. Methods The current study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Fatigue had relatively high impact on perceived "Function" and "Well-being," which is congruent with QoL and fatigue being strong determinants for work productivity loss in IBD. [7][8][9]30 There was low correlations between variables related to disease activity and fatigue at baseline as well as during VDZ therapy. 4,6,8,30 Concordantly, we have previously proposed that fatigue may represent a systemic extraintestinal disease manifestation that is largely independent of disease activity, chronicity, or nutritional deficiencies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Fatigue had relatively high impact on perceived "Function" and "Well-being," which is congruent with QoL and fatigue being strong determinants for work productivity loss in IBD. [7][8][9]30 There was low correlations between variables related to disease activity and fatigue at baseline as well as during VDZ therapy. 4,6,8,30 Concordantly, we have previously proposed that fatigue may represent a systemic extraintestinal disease manifestation that is largely independent of disease activity, chronicity, or nutritional deficiencies.…”
Section: Discussionmentioning
confidence: 94%
“…[7][8][9]30 There was low correlations between variables related to disease activity and fatigue at baseline as well as during VDZ therapy. 4,6,8,30 Concordantly, we have previously proposed that fatigue may represent a systemic extraintestinal disease manifestation that is largely independent of disease activity, chronicity, or nutritional deficiencies. 3,6,31,32 Most QoL and fatigue measures rely on comprehensive and time-consuming questionnaires which can be challenging to incorporate into a routine clinical monitoring program.…”
Section: Discussionmentioning
confidence: 94%
“…” (in Dutch: “ In hoeverre heeft u last gehad van vermoeidheid in de afgelopen 24 uur? ”) 8 Answers to this item were based upon a visual analogue 10-point Likert scale, ranging from a score of 1 (being not fatigued at all) to 10 (being severely fatigued) (Supplementary Fig. S4 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have linked inflammatory disease activity to fatigue in various chronic diseases, including IBD, but also in cancer, rheumatic- and autoimmune diseases 3 , 7 . In patients with IBD, the severity of fatigue has been associated with higher disease activity as measured by clinical disease activity scores 8 , 9 . In contrast, other studies have demonstrated that fatigue is not dependent on disease activity, and that it may even increase in patients who are in remission 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Only patients with quiescent IBD were included to avoid the wellknown influence of disease activity on IBD-related fatigue, for which the first step is optimizing IBD treatment. 38,39…”
Section: Impactmentioning
confidence: 99%